2009
DOI: 10.1002/rcm.4107
|View full text |Cite
|
Sign up to set email alerts
|

Negative ion fragmentations of deprotonated peptides. The unusual case of isoAsp: a joint experimental and theoretical study. Comparison with positive ion cleavages

Abstract: The following peptides have been examined in this study: GLDFG(OH), caeridin 1.1 [GLLDGLLGLGGL(NH(2))], 11 Ala citropin 1.1 [GLFDVIKKVAAVIGGL(NH(2))], Crinia angiotensin [APGDRIYVHPF(OH)] and their isoAsp isomers. It is not possible to differentiate between Asp- and isoAsp-containing peptides (used in this study) using negative ion electrospray mass spectrometry. This is because the isoAsp residue cleaves to give the same fragment anions as those formed by delta and gamma backbone cleavage of Asp. The isoAsp f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 42 publications
0
19
0
1
Order By: Relevance
“…All the above-mentioned MS methods were accomplished in the positive ion mode; however, in the negative ion mode, the isoAsp-containing peptides were not differentiated. 42 …”
Section: Introductionmentioning
confidence: 99%
“…All the above-mentioned MS methods were accomplished in the positive ion mode; however, in the negative ion mode, the isoAsp-containing peptides were not differentiated. 42 …”
Section: Introductionmentioning
confidence: 99%
“…These proceed through: (i) homolytic cleavage where loss of a radical forms a stable radical anion; (ii) formation of an anion complex; (iii) proton transfer toward the deprotonated site thus forming a new anion; and (iv) rearrangement reactions. Positive‐ and negative‐ion fragmentation pathways of peptides can be very different and they can thus provide useful complementary structural information . In addition, the negative‐ion fragmentation reactions of peptides are useful in the identification of post‐translational modifications as well as in peptide sequencing due to the more complete series of backbone product ions …”
mentioning
confidence: 99%
“…Due to the similarity between electron-transfer dissociation (ETD) and ECD, differentiation of aspartic and isoaspartic acid using ETD is also possible by detecting the presence of c + 57 and z • − 57 peaks [17]. However, recently, Hayley et al have shown that four out of eight peptides in their study did not give useful ETD spectra in positive ion mode [18]. For the rest of the peptides, c + 57 and z • − 57 ions were detectable but in very low abundance, and therefore there are difficulties to characterize aspartic and isoaspartic acid in doubly charged peptides.…”
mentioning
confidence: 99%